Minority shareholder's remedies - Boyle, A. J. (Cambridge University Press, 2002)
The state of English company law on minority shareholders' remedies is analysed in the light of the UK Law Commission, further appraised by the Company Law Review Steering Group. As well as considering the complexities of derivative actions and statutory minority remedies, Boyle discusses future directions for minority shareholders' remedies.
Keywords: Stockholders' derivative actions -- Great Britain.; Minority stockholders -- Legal status, laws, etc. -- Great Britain.; Remedies (Law) -- Great Britain.; Actions dérivées -- Grande-Bretagne.; Voies de droit -- Grande-Bretagne.; LAW -- Administrative Law & Regulatory Practice.; Minority stockholders -- Legal status, laws, etc.; Remedies (Law); Stockholders' derivative actions; Great Britain; Electronic books.